DEVELOPER’S PERCEPTION ON THE BARRIERS OF GREEN RATING SYSTEM IMPLEMENTATION IN MALAYSIA - Abdul Tharim, Asniza Hamimi; Yuserrie, Farid Al Hakeem; Youszelan, Nur Humaira Binti; Zainol, Halmi; Ahmad, Asmalia Che (Jurnal Arsitektur dan Perencanaan (JUARA), 2019)
This paper aimed to explore the developer’s perception on the implementation of Green Rating System in Malaysia. There had been a lot of negativity in the construction industry in Malaysia to achieved sustainable environment. 55 respondents from various developers were analysed to obtain the barriers of Green Rating system implementation varied from social barrier, financial barrier, economic barrier, knowledge barrier, technology barrier and political barrier accordingly. An in depth study on specific Green Rating System of Malaysia is highly suggested in the future.